Surface Modification of Activated Carbon for Enhancement of Nickel(II) Adsorption - A. Edwin Vasu (E-Journal of Chemistry)
A carbon prepared from coconut shells by simple carbonization was oxidized with different oxidizing agents, namely, hydrogen peroxide, ammonium persulphate and nitric acid. The surfaces of the unoxidized and oxidized carbons were characterized by Boehm and potentiometric titrations and IR spectra. The carbon materials prepared were tested for their ability to remove Ni(II) ions from aqueous solutions by batch mode adsorption experiments. Oxidations increased the surface acidic groups on the carbon which resulted in increased affinity of the carbon towards Ni(II).